A compact and high gain circularly polarized antenna for CubeSat S-band application
This project focuses on a compact antenna with high gain and circular polarization for S-band CubeSat application. CubeSat is categorized as a type of pico-satellite with a dimension of 10 x 10 x 10 cm3. By utilizing the component-of-the-shelf (COTS), this class of pico-satellite is capable of reducing the development cost and time compared to commercial satellites in segments such as space research, earth observation, inter-satellite communication, and the educational purpose. Due to the CubeSat’s size and weight constraints, most of their antennas are integrated with deployment mechanisms. One of the most popular deployable mechanisms used in CubeSats is the tape spring mechanism. In this project, two types of high gain circularly polarized antenna is designed to comply with 1U and 3U CubeSat at S-band frequency. A compact circularly polarized antenna is designed with a size of 55 x 55 x 0.85 mm3. The antenna operates with at least -10 dB of reflection coefficient, at least 3 dB of axial ratio and a gain of 3.84 dBi at 2.4 GHz. The antenna propagates with a right-handed circular polarization (RHCP) at 0° azimuth, and left-handed circular polarization (LHCP) at 180° azimuth. Such gain level needs to be improved for long-range CubeSat communication. A reflectarray is then designed to obtain an improved simulated gain of 10.49 dBi, satisfactory impedance and axial ratio bandwidth, with propagation directed at 29° azimuth. Despite its overall larger size of 297 x 330 x 0.635 mm3, and a focal length of 243 mm, it is still applicable for a 3U CubeSat together with a tape spring based deployment mechanism. Meanwhile, the reflectarray feed is also integrated on the CubeSat with its separate deployment mechanism. The initially designed circularly polarized antenna is also integrated with an artificial magnetic conductor (AMC) plane, which resulted in both gain enhancement and back radiation reduction. Since the initial antenna produces a bidirectional radiation pattern, the AMC plane reduced its back radiation and converting it into a unidirectional pattern. With a dimension of 99 x 99 x 21.485 mm3, the AMC plane increased the gain up to 7.7 dBi with RHCP mode. Besides that, a 19.16 % 10 dB impedance bandwidth and 10.4 % of 3 dB axial ratio bandwidth are achieved at 2.4 GHz. Due to the required gap of 20 mm between antenna and AMC plane, it has been integrated on the CubeSat using a simple spring coil deployment mechanism.